A case report of FATCO syndrome: fibular aplasia, tibial campomelia, and oligosyndactyly. Issue 1 (January 2015) - Bastaki, Laila A.; Al-Hathal, Muneef; Sadik, Doaa I.; Alrohaif, Hadil E.; Yousef, Hala Y.; Khallaf, Mohamed G.
Abstract : We report a male newborn with a rarely described congenital limb deficiency, fibular aplasia, tibial campomelia, and oligosyndactyly (FATCO) syndrome. This syndrome consists of shortening and anterior bowing of the lower limbs at the distal third of the tibia associated with overlying soft tissue dimpling and oligosyndactyly of the feet. Radiographic examination revealed complete absence of the fibula, tibial campomelia, and oligosyndactyly. Femora, humeri, ulnae, and radii were normal. To date, 12 cases have been published worldwide. The etiology of this syndrome is still unknown.